Plan de negocios para la creación de un centro artesanal en el cantón Quevedo, año 2014 - Cansing Mendoza, Carolina Jesús (2015)
This research seeks to analyze the craft market Quevedo canton to implement an artisanal crafts center that marketed directly to domestic and foreign tourists visiting the county, so it was necessary to design a business plan. The main objective of this business plan is to create a craft center established marketing handicrafts from all regions of Ecuador and the Quevedo canton becomes a city of innovative entrepreneurship for the benefit of the consumer in this way promote service quality that meets market needs. To carry out this business plan was necessary to study the craft Quevedo market where supply and demand for handmade products which showed a high demand is met. A marketing plan which established the product, place, promotion and price shopkeeper each of the crafts thus becoming attractive products for tourists was structured. It was necessary to implement a technical study to identify the operating process craft center in the canton Quevedo, thereby allowing for the economic study which determined the feasibility of investment with an internal rate of return of 57% which shows that it is feasible to invest a craft center. The NPV for this project is $ 53.661,49, 46 which means that the value of money over time the business plan is profitable.